An evidence-based guideline for children presenting with acute breathing difficulty. Issue 12 (24th November 2009) - Lakhanpaul, M; MacFaul, R; Werneke, U; Armon, K; Hemingway, P; Stephenson, T
Abstract : Objective: The aim of this study was to develop an evidence-based guideline for use primarily by junior clinicians to assist with the management of children presenting to the hospital with an acute breathing difficulty. Methods: An overview of the literature provided a framework of clinical questions for the management of a child with an acute breathing difficulty on which to base a systematic literature review. Relevant articles were appraised by the research fellow and graded according to their quality. A national panel of 50 clinicians was provided, by post, with the clinical questions, research papers, appraisals and the grades of recommendations generated. They were asked to check the grades allocated to the recommendations and the accuracy of the language used. They were also provided with all the clinical questions for which there was insufficient evidence to reach a conclusion but for which a consensus recommendation was required. A Delphi method was used to formalise the consensus process. For all recommendations, panel members were asked to rate their level of agreement on a 1–9-point Likert scale. The results of the first round were fed back, and appropriate alterations to the recommendations made or additional recommendations included. The process of rating was repeated, and the final guideline was developed based on the consensus reached. Results: Following two iterative rounds, the guideline was completed as a full technical document, with a series of key recommendations and an algorithm. It was based on 10 grade A (evidence from systematic review or meta-analyses), 5 grade B, 17 grade C and 31 grade D (consensus or expert opinion) recommendations. Conclusion: We have developed an evidence-based guideline that has subsequently been successfully implemented in the paediatric emergency departments and disseminated nationally. Results showing the effect of the guideline upon practice will be published separately.